Biodiversity of wild bees in Cyprus: Species richness, land use effects and contribution to ecosystem services - Varnava, Androulla (My University, 2022)
Wild bees are key providers of pollination services. Eighty-seven of the leading global food crops rely on animal pollination, with ca. 35% of global food supply depended on the service. Seminal work by multiple authors documented alarming declines in wild bee species in several parts of the world, with climate change and land use change, including intensive agriculture, emerging as key drivers of species declines. The goals of the current Dissertation were to evaluate wild bee diversity in Cyprus, investigate the effect of land use on species richness using historical and contemporary data, and document the contribution of specific species to pollination services. In Chapter 2 the first modern checklist of the wild bees of Cyprus was created, based on a compilation of previous publications, museum specimens and recent collections. Overall, 369 verified bee species have been recorded on the island, with eleven species reported from Cyprus for the first time. The island hosts all six of the globally widespread bee families, with Apidae represented by 110 species, Megachilidae with 91, Andrenidae with 76, Halictidae with 72, Colletidae with 19, and Melittidae with 1. Twenty-one of the recorded bee species are endemic (i.e., 5.7 % endemism rate) and Cyprus ranks third after Lesvos and Sicily in known bee species richness among the Mediterranean islands. In Chapter 3 we relied on a unique data set collected by the bee taxonomist George Mavromoustakis covering a 30-year period beginning 100 years ago, and recent biweekly samplings over two years to analyze changes in species richness. We focused on two areas with contrasting land use patterns: Cherkes Chiftlik - Asomatos (CC_Asomatos) with a mainly agricultural and Akrotiri with a mainly seminatural land use profile. Changes in landscape use categories were mild and relatively similar in the two areas, with urban development more scattered in CC_Asomatos. In addition, CC_Asomatos experienced drastic changes in land use intensity, with an increase in the use of high-input agricultural methods, including synthetic insecticides, beginning with DDT from around 1945. We detected a substantial species turnover, with 43 species collected only in historical samples, 77 only in recent samples, while 42 persisted in both periods. Mavromoustakis reported 50 species from Akrotiri and 80 from CC_Asomatos, out of which 26 were common. We collected 110 species from Akrotiri, and 68 from CC_Asomatos with 53 common. There was a statistically significant difference in the frequency of species extinctions, with CC_Asomatos loosing species at twice the rate of Akrotiri, at ca. 75 and 35% respectively. The richness of plants visited by bees was higher in Akrotiri, with a significant relationship between plant species richness and bee species richness. We hypothesize that the main drivers for species extinctions are the intensive use of synthetic pesticides, and the loss of habitat and floral diversity because of the expansion of agriculture and urban development. Thirteen species new to Cyprus, as well as three species new to science are reported as part of the current work. Chapter 4 assessed the diversity of wild bees and other pollinators relying on carob flowers, as well as the contribution of animal pollination to carob production. Carob flowers were subjected to two treatments: Open pollination, where inflorescences were left untreated, and wind pollination, where inflorescences were bagged in a mesh during blooming. Weekly observations during blooming showed that Apis mellifera was the most frequent floral visitor followed by wild bees and wasps. Carob flowers were visited by at least 10 different wild bee species. Open-pollinated flowers produced significantly more pods, with the benefit ranging from 4 to 20 times higher production, depending on the region. Open pollination led to pods with greater weight, length and number of seeds compared to pods derived from wind pollination. The results of the study highlight the importance of animal pollination to carob production, as well as the significance of carob trees to wild bee conservation. The findings of the current dissertation highlight the importance of historical data in understanding bee diversity and the need for establishing a long-term monitoring program and conservation actions for the bee species of Cyprus.
Keywords: Wild bees; Cyprus; Wild bee diversity; Άγριες μέλισσες; Κύπρος; Βιοποικιλότητα άγριων μελισσών